Supporting older adults in using technology for lifelong learning: The methodological and conceptual value of Wizard of Oz simulations - Eynon, Rebecca; Davies, Chris; Holmes, Wayne (Proceedings of the International Conference on Networked Learning, 2012)
In the past, many technological initiatives have failed to engage adult learners in any significant way in part due to the lack of technological initiatives that build on people’s existing interests but also because of an insufficient focus on designing co-operative technologies that can be used effortlessly. In this paper we provide our experiences of the use of Wizard of Oz (WOz) studies in order to develop a technological tool to support older adults’ use of the Internet for learning, where we aimed to achieve a more learner centred approach to design. Wizard of Oz simulation is a research method common in Human-Computer Interface (HCI), Natural Language Processing (NLP) and other human factors/computer usability research where researchers conceal themselves from research participants and use communications technology to pretend that a prototype or incomplete computer-based conversational system is fully functioning. The purpose of a WOz simulation is usually to investigate and inform the development of a technology that has yet to be developed, or to learn more about how people interact with the system in order to improve the design. In this paper we outline the understandings we developed using this technique, highlighting the methodological and conceptual value of using this approach. Based on conducting Wizard of Oz simulations with 20 older adults with a diverse range of educational backgrounds and technological expertise we ask: what are the methodological benefits and challenges of using Wizard of Oz simulations in studies of learning and the Internet? In this paper, we argue that the use of Wizard of Oz approach could be a valuable method to employ for a wider range of research that examines networked learning in formal or informal settings. This is particularly the case as one (unanticipated) effect of the study was how the use of this technique developed our understandings of the everyday experiences older adults have with computers and the Internet when trying to learn new things. In addition we argue that the use of this method is important in the current context where a common criticism of technologies that are designed to support learning tend not to be fit for purpose, as they have either been developed initially for commercial uses or developed without a strong understanding of the learner in mind.